2018
DOI: 10.1186/s12991-018-0184-4
|View full text |Cite
|
Sign up to set email alerts
|

Exploring PTSD in emergency operators of a major University Hospital in Italy: a preliminary report on the role of gender, age, and education

Abstract: BackgroundEmergency services personnel face frequent exposure to potentially traumatic events, with the potential for chronic symptomatic distress. The DSM-5 recently recognized a particular risk for post-traumatic stress disorder (PTSD) among first responders (criterion A4) but data are still scarce on prevalence rates and correlates.ObjectiveThe aim of the present study was to explore the possible role of age, gender, and education training in a sample of emergency personnel diagnosed with DSM-5 PTSD.Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
62
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(75 citation statements)
references
References 43 publications
9
62
0
4
Order By: Relevance
“…Conversely, quarantining negatively affected mental health, increasing GSI of 0.05 for each week passed in lockdown. Consistent with previous studies (Di Giuseppe et al, 2019cGiuseppe et al, , 2020cCarmassi et al, 2014Carmassi et al, , 2018, younger subjects and females were at higher risk for mental health problems, while living with one's spouse resulted in them feeling slightly protected in terms of psychological wellbeing. The protective factor of mindfulness disposition and training has already been shown in previous literature, influencing positively memory function, cognitive resilience, mental health, emotional balance, and high stress functioning, also decreasing anxiety, depression, and burnout levels (Jha et al, 2010(Jha et al, , 2017Abenavoli et al, 2013;De Frias and Whyne, 2015;Westphal et al, 2015;Xu et al, 2017).…”
Section: Discussionsupporting
confidence: 90%
“…Conversely, quarantining negatively affected mental health, increasing GSI of 0.05 for each week passed in lockdown. Consistent with previous studies (Di Giuseppe et al, 2019cGiuseppe et al, , 2020cCarmassi et al, 2014Carmassi et al, , 2018, younger subjects and females were at higher risk for mental health problems, while living with one's spouse resulted in them feeling slightly protected in terms of psychological wellbeing. The protective factor of mindfulness disposition and training has already been shown in previous literature, influencing positively memory function, cognitive resilience, mental health, emotional balance, and high stress functioning, also decreasing anxiety, depression, and burnout levels (Jha et al, 2010(Jha et al, , 2017Abenavoli et al, 2013;De Frias and Whyne, 2015;Westphal et al, 2015;Xu et al, 2017).…”
Section: Discussionsupporting
confidence: 90%
“…Further, it is possible to hypothesize a consequent and related impact of professional quality-of-life dimensions on mental health outcomes. The same independent variables (HCW characteristics) obviously present a direct impact on HCWs’ mental health, which is completely independent of the pandemic, as highly demonstrated by the literature on HCWs through years [ 28 , 29 , 30 ]. (See Figure 1 for theoretical model of study hypothesis).…”
Section: Introductionmentioning
confidence: 92%
“…The scientific community has called for high-quality evidence on the mental health effects of the COVID-19 pandemic across the whole population and vulnerable groups such as HCWs, which has since confirmed that data on this challenging issue are still limited [ 28 ]. In this context, it is therefore an essential contribution to literature in order to better understand the effects of COVID-19 pandemic on HCWs’ outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, positive behaviors such as healthy eating, sport practicing and sleeping an adequate number of hours have shown to impact and reduce the impact of stress [30]. Many other strategies have also shown to be effective, such as the implementation of debrie ng sessions and group therapies to share experiences and relieve the sorrow related to challenging and stressful situations.…”
Section: Need For Psychological Supportmentioning
confidence: 99%